Application of Moringa Leaf Extract (Moringa oleifera) During Post-Ripening Period on the Physiological Quality of Ciherang Rice Seeds (Oryza sativa L.) - Neetha Elinda; Ida Retno Moeljani; Makhziah Makhziah (The University of Lampung, 2025)
This research investigates the effects of Moringa leaf extract and post-ripening periods on the physiological quality of Ciherang rice seeds, which often exhibit dormancy after harvest. Effective methods are needed to break this dormancy to achieve optimal planting results. Moringa leaf extract, recognized as a sustainable and eco-friendly biostimulant, was tested for its potential to enhance seed quality. The study utilized a robust experimental design, testing four concentrations of Moringa leaf extract (0%, 20%, 60%, and 100%) across four post-ripening periods (0, 2, 4, and 6 weeks), with three repetitions for each treatment. A multiple observation data analysis was conducted, combining individual measurements with time-grouped assessments. Results revealed that both the concentration of Moringa leaf extract and the length of the post-ripening period significantly influenced the physiological quality of the seeds. The most effective treatments were identified as 60% Moringa leaf extract with a 4-week post-ripening period and 20% extract with a 6-week period. This research underscores the potential of Moringa leaf extract as an accessible and environmentally friendly method for breaking seed dormancy, offering valuable insights for farmers aiming to improve seed germination and enhance crop productivity in regions where Moringa is abundant. Keywords: Ciherang, Moringa Leaf Extract Concentration, Physiological Quality, Post-ripening, Rice Seeds.